Clinical spectrum and histopathological analysis of cervical lymphadenopathy: a rural hospital study - Veetil, Sreejith Kannummal; Sharma, Binni (International Surgery Journal, 2020)
Background: The analysis of lymph node enlargement in the neck is not an easy task. These diseases which can be neoplastic also demands correct diagnosis for further management. The study intended to find out systematically the various pathological conditions presenting with enlarged lymph nodes in the neck, also the various modes of clinical presentation and behaviour of these conditions. Methods: The study population consisted of patients above 12 years presenting with cervical lymph node enlargement. The proforma which was drafted is used. Patient was examined systematically giving utmost importance to local examination. After making a clinical diagnosis, further relevant investigations were done to confirm the diagnosis. Treatment was instituted appropriately and followed up the patients. Results: Majority of the cases in this study had non-neoplastic causes for cervical lymphadenopathy in which tuberculosis is most common. Posterior triangle group of lymph nodes was most commonly affected in tuberculosis. Variable results were noted among the groups of lesions, with regard to local characteristics like number, laterality, mobility and involvement of other group of lymph nodes, etc. FNAC by virtue of it being inexpensive, quick in getting the results and easy to perform, is one of the important and essential diagnostic procedures. Conclusions: As cervical lymphadenopathy is an important disease, it always calls for meticulous attention, analysis and treatment. FNAC is found to be a frontline investigation of choice with biopsy and histopathological examination done for confirmation. Most of the non-neoplastic lesions are medically curable with limited role for surgery.